1982
DOI: 10.1111/j.1432-1033.1982.tb06826.x
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocorticotropic Hormone and α‐Melanocyte‐Stimulating Hormone Induce Secretion and Protein Phosphorylation in the Rat Lacrimal Gland by Activation of a cAMP‐Dependent Pathway

Abstract: In the present study a CAMP-dependent pathway leading to exocytosis in the rat lacrimal gland was investigated in detail. Using a lobule system in vitro, adrenocorticotropic hormone (corticotropin) and a-melanocyte-stimulating hormone (cr-melanotropin) stimulated protein discharge almost equally effective as dibutyryladenosine 3',5'-monophosphate (Bt2cAMP) and 3-isobutyl-I-methylxanthine but less potent than carbamoylcholine. Maximal stimulation was obtained at a hormone concentration of 20 nM for both peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(17 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…Further analysis of lacrimal gland enzyme secretion stimulated by cyclic AMP demonstrated that IBMX-induced secretion was partially dependent upon extracellular Ca2+, although not to the same extent as carbachol-induced secretion. In this connexion Jahn et al (1982) found that adrenocorticotrophic hormone (ACTH) stimulates rat lacrimal gland [3H]leucine discharge by utilizing cyclic AMP. In one experiment they found ACTH-induced secretion to be almost unaffected by incubation in Ca2+-free medium containing 0.1 mM-EGTA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further analysis of lacrimal gland enzyme secretion stimulated by cyclic AMP demonstrated that IBMX-induced secretion was partially dependent upon extracellular Ca2+, although not to the same extent as carbachol-induced secretion. In this connexion Jahn et al (1982) found that adrenocorticotrophic hormone (ACTH) stimulates rat lacrimal gland [3H]leucine discharge by utilizing cyclic AMP. In one experiment they found ACTH-induced secretion to be almost unaffected by incubation in Ca2+-free medium containing 0.1 mM-EGTA.…”
Section: Resultsmentioning
confidence: 99%
“…In one experiment they found ACTH-induced secretion to be almost unaffected by incubation in Ca2+-free medium containing 0.1 mM-EGTA. One explanation for the inability of Jahn et al (1982) to detect Ca2+ dependency of cyclic-AMP-mediated secretion could be that they did not compare ACTH-induced secretion in the presence and absence of Ca2+ in the same experiment. Instead they compared ACTH-induced secretion to basal secretion, both in the absence of Ca2+.…”
Section: Resultsmentioning
confidence: 99%
“…During stress, the circulating levels of melanocortin peptides: adrenocorticotropic hormone (ACTH) and ␣-melanocyte-stimulating hormone (␣-MSH) are increased dramatically. 1,54 ACTH and ␣-MSH induce protein secretion [55][56][57] and phosphorylation 55 in the lacrimal gland. There is evidence for specific receptor binding sites of melanocortin receptors in the lacrimal gland.…”
Section: Discussionmentioning
confidence: 99%
“…It was initially suggested that the ACTH receptor gene would provide the link to explain the association of the three main features of the syndrome because of evidence that ACTH has some neurotropic effects, 16 as well as the demonstration that ACTH binds to rat lacrimal glands. 17 However, in the absence of any documented mutation in the ACTH receptor in the triple A syndrome, 1,15 and the current evidence that the ACTH receptor gene is not expressed outside the adrenal cortex, 18 it is unlikely that mutations in the ACTH receptor gene would account for any of the three main features of the disorder. Ongoing studies designed to identify the defective gene and its product will probably provide the explanation.…”
Section: Discussionmentioning
confidence: 99%